En kritisk studie av bolagets ansvar vid fel eller brister i prospekt - Klarin,Martin (2014)
The purpose of this essay is to from critical perspective examine today’s legal position and clarify whether a company can become liable for errors or omissions in a prospectus. Sweden has for a long time had a restrictive attitude to impose any liability for pure economic loss. The responsibility for errors or omissions in a prospectus is an area where the strictness becomes clear. Only for one group of responsible entities, the company bodies, are there clear rules if and when it is possible to succeed with an action for damages. However, for the most natural responsible entity, the company, the legal position is very unclear. A common opinion in the doctrine and preliminary works is that a company cannot become liable to a subscriber of shares for errors or omissions in a prospectus. Nor can the misled subscriber get the subscription of shares annulled. The reason for this approach is not rooted in regulation or in a statement in a preliminary work, but in a renowned court case from 1935, NJA 1935 p. 270, and in an article in SvJT from 1938 by Hjalmar Karlgren. NJA 1935 p. 270 does not elaborate on errors or omissions in a prospectus, nor does the main issue seem to have been about the company's liability. But in doctrine and preliminary works the widespread perception is that it still is possible to deduce that HD did come to the conclusion that it is not possible to impose a liability on the company for errors or omissions in a prospectus. A key element to this interpretation to becoming the prevailing position is Karlgrens article from 1938. Karlgren argues that it possible to deduce, from the judgment in NJA 1935 p. 270, that HD have come to the conclusion that it is not possible to annul a subscription of shares, and because of that it follows that it is neither possible to succeed with a claim for damages against the company. In my opinion, it is fair to question whether these legal sources of old age and uncertain value should govern today’s law. The most natural would be that a company could be held responsible for errors or omissions in a prospectus. A company have through the subscription of shares a close relationship to the investor. This relation can be described as a contract or at least as quasi-contractual, and the company is often in a much better financial position than the other potential responsible entities, which makes it better fit to pay out large damages. Overall, the present legal situation is unclear, but indications are that it is possible to find success with an action for damages against the company for errors or omissions in a prospectus. However, in a modern constitutional state that alludes to be a key part of the global capital market, there should be a law that gives misled investors the right to hold the company liable for errors or omissions arising in a prospectus. Hopefully the legislator will recognize this in the near future and introduce the legislation which the Swedish securities market deserve.
Keywords: associationsrätt; prospekt